Analysis Of Company Reputation And Brand Attachment On Repurchase Intention In A CV GUNUNG MAS: The Mediating Role Of Customer Satisfaction And Brand Commitment In East Java - Hartono, Fransiskus; Hongdiyanto, Charly (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research investigates how company reputation and brand attachment influence repurchase intention in the B2B sugar sector, with customer satisfaction and brand commitment as mediating variables. The study focuses on distributors and retailers in East Java, a key sugar distribution hub in Indonesia. A quantitative approach was employed, utilizing purposive sampling to survey 97 retail partners actively involved in sugar transactions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings are expected to reveal that strong company reputation and emotional brand attachment positively influence repurchase intention, both directly and indirectly through increased satisfaction and commitment. This research provides empirical evidence and managerial insights for sugar companies to enhance long-term B2B loyalty by strengthening relational brand strategies. By highlighting emotional and reputational factors over transactional elements like price, the study contributes to a deeper understanding of loyalty drivers in commodity-based industries.